Suhu Tubuh Bayi Prematur di Inkubator Dinding Tunggal dengan Inkubator Dinding Tunggal Disertai Sungkup - Padila Padila; Ida Agustien (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to compare the average change in body temperature in a single wall incubator with a single wall incubator with hood in preterm infants with hypothermia. The design of this study uses a comparative descriptive method. The results of the study in the group of preterm infants with hypothermia in a single wall incubator with a lid significantly increased mean body temperature changes with a mean value of 36.09 variance 0.152 while for preterm infants with hypothermia in a single wall incubator a mean value of 35.35 variance values 0.859 and obtained t count from the two study groups namely 2.551 and 1.717 t table. In conclusion, a single wall incubator with a lid increases body temperature in premature infants with hypothermia compared to a single wall incubator. Keywords: Hypothermia, Incubator, Premature